Implementation of international legal norms in the field of protection and preservation of the World Ocean from pollution into legislation of the Russian Federation: historical aspect and modernity - A. I. Abdullin; K. B. Valiullina (Московский журнал международного права, 2024)
INTRODUCTION. The world ocean is the main component of the Earth's biosphere, a key element of the hydrosphere containing 95% of all water on the planet, the most important link in the ecological system, a source of mineral, biological and strategic resources. Nevertheless, the rapid growth of the population, the development of new territories, the rapid development of the economy and the increasingly intensive use of the spaces and resources of the World Ocean in this regard have led to serious and sometimes irreversible consequences that negatively aﬀect its condition. The Russian Federation, being a leading maritime Power, takes an active position in taking urgent measures to ensure the protection and preservation of the waters and resources of the World Ocean. Realizing the impossibility of resolving the environmental problem that has arisen on the basis of exclusively universal or regional agreements, as well as by taking appropriate measures at the domestic level, recognizing that the need to ensure the protection and preservation of the oceans from pollution requires an exclusively holistic approach to the regulatory regulation of this issue, the Russian Federation expressed its desire to cooperate on the most important issues of ensuring global environmental problems, where the protection and preservation of the oceans from pollution is one of the priority areas of activity.MATERIALS AND METHODS. This study uses the works of both Russian and foreign experts in the ﬁeld of international environmental and international maritime law. The research used general scientiﬁc methods of cognition – analysis, synthesis, induction, deduction. Special legal methods were also used in the work – formal legal, technical legal, the method of legal analogy, as well as the comparative legal method.THE RESULTS OF THE STUDY. The analysis of the current practice on the implementation of international legal norms in the ﬁeld of protection and preservation of the world ocean from pollution in the legislation of the Russian Federation allowed us to conclude that the protection of the World Ocean from pollution is a system of legal relations requiring coordinated actions of international law and national legislation.DISCUSSIONS AND CONCLUSIONS. Within the framework of the study, the author comes to the logical conclusion that the norms of international and national law should act in unity in order to comply with the natural processes of development of activities in the world Ocean and the interests of states. The protection and preservation of the World Ocean is a complex task that requires both a comprehensive regulatory and legal regulation at all levels, and the formation of a correct public consciousness about its integrity, unity and value of this unique, most important component of the Earth's hydrosphere, allowing the world community to unite in organizing cooperation on issues of ensuring global security of the entire civilization on a democratic basis.